A case–control study of the interaction of fetal heart rate abnormalities, fetal growth restriction, meconium in the amniotic fluid and tachysystole, in relation to the outcome of labour. (9th October 2022) - Steer, Philip J.; Yau, Christopher W. H.; Blott, Maggie; Lattey, Katherine; Nwandison, Millicent; Uddin, Zeenath; Winter, Cathy; Draycott, Timothy
Abstract: Objective: To quantify the incidence of intrapartum risk factors in labours with an adverse outcome, and compare them with the incidence of the same indicators in a series of consecutive labours without adverse outcome. Design: Case–control study. Setting: Twenty‐six maternity units in the UK. Population or sample: Sixty‐nine labours with an adverse outcome and 198 labours without adverse outcome. Methods: Observational study. Main outcome measures: Incidence of risk factors in hourly assessments for 7 hours before birth in the two groups. Results: A risk score combining suspected fetal growth restriction, tachysystole, meconium in the amniotic fluid and fetal heart rate abnormalities (baseline rate and variability, presence of decelerations) gave the best indication of likely outcome group. Conclusions: Accurate risk assessment in labour requires fetal heart rate abnormalities to be considered in context with additional intrapartum risk factors.